Produtos farmacêuticos e de higiene pessoal no rio Iguaçu e seus afluentes - Ide, Alessandra Honjo (2014)
Water quality is a currently subject that has attracted the attention of people from all areas, especially the contamination of aquatic environments by so-called emerging pollutants. These contaminants are organic or inorganic, natural or synthetic compounds, contained in products used throughout the population and that reacht water bodies. With this work, we intended to verify the presence of pharmaceuticals and personal care products (caffeine, acetylsalicylic acid, salicylic acid, ketoprofen, naproxen, gemfibrozil, fenofibrate, estradiol, ethinylestradiol, estrone, 4– methylbenzylidencamphor, octylmethoxycinnamate and octacrilene) in Iguaçu River, from source to mouth, and its major tributaries in the Metropolitan Region of Curitiba. The determination of emerging contaminants was done using solid phase extraction and liquid chromatography with diode array detector and gas chromatography tanden mass spectrometry. Validation of the methodology was conducted in accordance with standards established by the Agência Nacional de Vigilância Sanitária. The method for extraction and quantitation of the 13 compounds proved to be efficient for the determination of 10 of these analytes in water samples. Caffeine was the main compound present in the samples; acetylsalicylic acid was the pharmaceutical product founded in the highest concentractions; estradiol, the female sexual hormone more frequently detected and octylmethoxycinnamate, the personal care product longer detected. The results of this study indicate intense anthropogenic influence in the Upper Iguaçu basin, mainly due to the presence of domestic sewage. It was also observed that the wastewater treatment plants contribute to the entry of nutrients and emerging contaminants that are not efficiently removed in the treatments used. The lack of sanitation has a negative impact on water quality of the Iguaçu river, which is highly degraded due to the influence of the tributaries of the Metropolitan Region of Curitiba.